The Impact of Social Support on Resilience Viewed from Exrovert and Introvert Personality Types in Islamic Boarding School Students - Savira Annisa Putri Suprapto (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Resilience is an important thing that must be owned by every individual, especially when facing difficulties in his life. Social support can be provided to increase resilience in individuals, so that they are able to rise from their adversity. Personality type is related to resilience and social support. The purpose of this study was to determine the effect of social support on resilience moderated by personality type. This research uses a quantitative approach. The sampling technique used stratified random sampling, and the number of students in the boarding school was 30 people. Measurements were made using the Multidimensional Scale of Percived Social Support (MSPSS), Connor Davidson - Resilience Scale (CD-RISC), and Eysenck Personality Questionnaire Short Scale. The results showed that support had no effect on resilience (p=0.1230) and personality type also could not support the effect of social support on resilience (p=0.103).